Management of Business Risk Hedging in Construction Contracts from the Perspective of Public Investors - Andrlová, Barbara; Korytárová, Jana (University North, 2020)
Risk management of construction projects presented in the article focuses on the management of business risk from the perspective of public investors in public works contracts in the Czech Republic. Based on the data analysis and a comparative study of specific attributes in contracts for works, the result of the research has been a portfolio of specific instruments and their recommended parameters for effective business risk management. Qualitative analysis was conducted using a questionnaire survey and structured interviews with public sector representatives to share their views on the current practice of protecting public procurement with regard to mitigate business risk. Types, functions and recommended parameters of hedging instruments has been proposed. Effective forms of hedging are mainly liability insurance for damage to things, property and health, contractual penalties, retention money and bank guarantees. Results of the research were compared with foreign practice and international contractual standards.

Risk management of construction projects presented in the article focuses on the management of business risk from the perspective of public investors in public works contracts in the Czech Republic. Based on the data analysis and a comparative study of specific attributes in contracts for works, the result of the research has been a portfolio of specific instruments and their recommended parameters for effective business risk management. Qualitative analysis was conducted using a questionnaire survey and structured interviews with public sector representatives to share their views on the current practice of protecting public procurement with regard to mitigate business risk. Types, functions and recommended parameters of hedging instruments has been proposed. Effective forms of hedging are mainly liability insurance for damage to things, property and health, contractual penalties, retention money and bank guarantees. Results of the research were compared with foreign practice and international contractual standards.
Management of Business Risk Hedging in Construction Contracts from the Perspective of Public Investors
Keywords: business risk management; construction project; contract for work; hedging instrument; public works contract; retention money; business risk management; construction project; contract for work; hedging instrument; public works contract; retention money